Select Masterpieces of Biblical Literature - Moulton, Richard G. (Richard Green), 1849-1924 (Salt Lake City, UT : Project Gutenberg, 2008)
"Select Masterpieces of Biblical Literature" by Richard G. Moulton is a literary collection written in the late 19th century. This volume serves as an introduction to a series that aims to present biblical texts in a modern literary format, focusing on the diverse literary forms within the Scriptures. The work seeks to restore the literary structure often lost in traditional presentations, allowing readers to appreciate the Bible both as sacred scripture and as a foundation of literary heritage. The opening of this text establishes Moulton's intent to delve into the literary richness of the Bible, emphasizing that what is commonly referred to as 'The Bible' is, in reality, a compilation of various genres, including history, wisdom literature, oratory, and poetry, among others. Moulton critiques the way traditional versions present biblical texts, arguing that they obscure the original literary intentions and structures. In this exploration, he outlines the necessity of appreciating the Bible for its myriad literary forms so that readers can engage with the narratives, poetry, and philosophical discourses on their own terms, while also providing a roadmap for understanding the selections featured in this series. (This is an automatically generated summary.)
Release date is 2008-12-12
E-text prepared by Stephen Hope, Fox in the Stars, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Bible. Old Testament -- Selections